Reducing renewable resource demand fluctuation using soft precedence relations in project scheduling - Jaskowski, Piotr; Biruk, Slawomir (Journal of Civil Engineering and Management, 2018)
Renewable resource levelling is the core of the scheduling process. A perfect schedule ensures that resource supply corresponds to the demand at every unit of project time. A classic approach to resource levelling in schedules with predefined project completion dates consists in manipulating processes start dates. Resource deployment can be also improved by considering alternative construction processes execution modes with various crew formations, and by allowing activities to be split. There are other possibilities: in many practical cases, the activities’ precedence logic predefined in the network model can be changed with no harm to the project outcome. Within the structure of the project network model, some precedence relations between activities would definitely be of fixed (hard) character, whereas some might allow the activities to be executed at the same time or arranged in a variety of logical sequences. The authors use soft precedence relations that let the processes run in reversed order or that can be cancelled, in search for improved resource usage profiles. The benefits of scheduling with soft precedence relations are demonstrated by an example.